A SCUBA diver with acute kidney injury. (6th May 2015) - Gleeson, Patrick James; Kelly, Yvelynne; Ni Sheaghdha, Eadaoin; Lappin, David
Abstract : An otherwise healthy young man was transferred to our hospital after a diving incident. He had made an uncontrolled ascent from 10 m. On arrival he appeared well. No hypotensive episodes occurred during the transfer. He denied having arthralgias, back pain, dyspnoea or neurological symptoms. Laboratory investigations revealed acutely elevated creatinine (170 µmol/L) and creatine kinase (909 U/L). Radiology was consistent with a focus of pulmonary barotrauma and intrinsic renal disease. Creatine kinase is a marker of arterial gas embolism (AGE). We determined that our patient suffered acute kidney injury as a result of gas embolisation to his renal vasculature from an area of pulmonary barotrauma. Creatinine fell the following day in response to aggressive intravenous fluids. This is the first reported case of acute kidney injury secondary to AGE. Biochemical studies should be part of the routine assessment of patients involved in diving incidents.